The Values Practice of Scriptures in Building Social-Religious Harmony in Kampung Laut - Eka Safitri; Ihsan Sa'dudin; Didin Nurul Rosidin (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Islam Negeri Profesor Kiai Haji Saifuddin Zuhri Purwokerto Purwokerto, 2022)
The purpose of this study is to describe the socio-religious life in Kampung Laut, Cilacap, Central Java, which lives in harmony and harmony in the midst of the diversity of beliefs that exist in society. The development of the Kampung Laut community has socio-religious characteristics for the southern coastal community. The diversity of the religious population is not a cause that can cause conflict in the Kampung Laut community. Muslims and Christians live without interfering with the worship practices and rituals of followers of other religions. The focus of this study is to analyze the interaction between religious communities, especially between Christians and Muslims in Kampung Laut as the implementation of the teachings of the Bible and the Qur'an. The specification of this research is descriptive qualitative, which is stated by the respondents in writing or verbally as well as real behavior, which is studied and studied in its entirety. The data that has been obtained is processed using the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions or verification. Research shows that Christians apply the values in the Bible and so do Muslims apply the teachings of the Qur'an in social life. Then, the values of harmony that they carry out in life are in the Holy Scriptures such as the Bible and the Qur'an which create harmony in social life.